Prevalence of metabolic syndrome and its associated risk factors among staffs in a Malaysian public university - Manaf, Mohd Rizal Abdul (Sci Rep, 2021)
Public health systems are concerned with the commensurate rise of metabolic syndrome (MetS) incidence across populations worldwide, due to its tendency to amplify greater risk of diabetes and cardiovascular diseases within communities. This study aimed to determine the prevalence of MetS and its associated risk factors among staffs in a Malaysian public university. A cross-sectional study was conducted among 538 staffs from the Universiti Kebangsaan Malaysia (UKM) between April and June 2019. MetS was defined according to JIS “Harmonized” criteria. A questionnaire that consisted of items on socio-demographics, lifestyle risk behaviors and personal medical history information was administered to participants. Subsequently, a series of physical examination and biochemical assessment was conducted at the hall or foyer of selected faculties in the university. Descriptive and inferential statistics were conducted using SPSS version 22.0. Multivariate models were yielded to determine the risk factors associated with MetS. Statistical significance was set at P < 0.05. The overall prevalence of MetS was 20.6%, with men having greater prevalence than women (24.9% vs. 18.3%). Prevalence of MetS increased with age. Factors contributed to MetS in the overall sample were BMI, hypertension, diabetes and physical activity of moderate intensity. Diabetes and hypertension were significantly associated with MetS in men, whereas BMI, diabetes and hyperlipidemia were significantly associated with MetS in women. Lifestyle behaviors and cardio-metabolic risk factors were associated with MetS for the overall sample, and across genders.